Why Patentees Litigate - Andrews, Damon C. (Science and Technology Law Review, 2011)
Several aspects of patent litigation call into question patent holders’ motivation for enforcing their exclusionary rights. Indeed, the expense alone can be enough to deter a firm from engaging in litigation, especially if it is likely that the parties will be unable to reach a settlement agreement and will go to trial. Notwithstanding, the number of patent infringement filings in district courts grows each year, thus providing a forum for asking what patent holders really desire to gain from litigating. Although injunctive relief and damages awards confer benefits to patent holders that can make litigating worthwhile, this Article posits that plaintiffs have no intention of ever obtaining these statutory remedies. Rather, handsome settlement arrangements provide the incentive for patentees to litigate. This Article contends that such settlement agreements are becoming a way of life for patent holders, and that rather than viewing litigation as an end result of parties’ failure to resolve a dispute, it is instead becoming the ordinary course of business and a routine consequence of owning a patent.